Effects of climate change on the distribution of Iberian tree species - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Applied Vegetation Science, 2008)
Question: Will the predicted climate changes affect species distribution in the Iberian Peninsula? Location: Iberian Peninsula (Spain and Portugal). Methods: We modelled current and future tree distributions as a function of climate, using a computational framework that made use of one machine learning technique, the random forest (RF) algorithm. This algorithm provided good predictions of the current distribution of each species, as shown by the area under the corresponding receiver operating characteristics (ROC) curves. Species turnover, richness and the change in distributions over time to 2080 under four Intergovernmental panel on climate change (IPCC) scenarios were calculated using the species map outputs. Results and Conclusions: The results show a notable reduction in the potential distribution of the studied species under all the IPCC scenarios, particularly so for mountain conifer species such as Pinus sylvestris, P. uncinata and Abies alba. Temperate species, especially Fagus sylvatica and Quercus petraea, were also predicted to suffer a reduction in their range; also sub-mediterranean species, especially Q. pyrenaica, were predicted to undergo notable decline. In contrast, typically Mediterranean species appeared to be generally more capable of migration, and are therefore likely to be less affected.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: 1990; 2002; amaral franco; avishai; for quercus pubescens; Forest distributions; govaerts; iberian peninsula; learning; machine; Machine learning; nomenclature; random forest

Effects of climate change on the distribution of Iberian tree species - Benito Garzón, Marta; Sánchez de Dios, Rut; Sainz Ollero, Helios (Applied Vegetation Science, 2008)
Question: Will the predicted climate changes affect species distribution in the Iberian Peninsula? Location: Iberian Peninsula (Spain and Portugal). Methods: We modelled current and future tree distributions as a function of climate, using a computational framework that made use of one machine learning technique, the random forest (RF) algorithm. This algorithm provided good predictions of the current distribution of each species, as shown by the area under the corresponding receiver operating characteristics (ROC) curves. Species turnover, richness and the change in distributions over time to 2080 under four Intergovernmental panel on climate change (IPCC) scenarios were calculated using the species map outputs. Results and Conclusions: The results show a notable reduction in the potential distribution of the studied species under all the IPCC scenarios, particularly so for mountain conifer species such as Pinus sylvestris, P. uncinata and Abies alba. Temperate species, especially Fagus sylvatica and Quercus petraea, were also predicted to suffer a reduction in their range; also sub-mediterranean species, especially Q. pyrenaica, were predicted to undergo notable decline. In contrast, typically Mediterranean species appeared to be generally more capable of migration, and are therefore likely to be less affected.
Keywords: 1990; 2002; amaral franco; avishai; for quercus pubescens; Forest distributions; govaerts; iberian peninsula; learning; machine; Machine learning; nomenclature; random forest

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder

Post-fire regeneration of Mediterranean plant communities at a regional scale is dependent on vegetation type and dryness - Arnan, Xavier; Rodrigo, Anselm; Retana, Javier (Journal of Vegetation Science, 2007)
Question: We tested whether (1) the change in composition and structure of whole plant communities after ﬁre is directly related to regeneration of the dominant tree species in the canopy; (2) the change in structure and composition of plant communities several years after ﬁre decreases with the proportion of obligate seeders and (3) the proportion of obligate seeders in plant communities increases with the dryness gradient. Location: Catalonia (NE Spain) Methods: We measured ﬂoristic differences between burned and long-since burned sites in eight vegetation types across a climate gradient. We compared 22 sites burnt in 1994 in paired plots with 22 sites that had not been burnt since the 1940s. In each site we placed plots in burned and long-since burned areas, where we identiﬁed the presence and abundance of all plant species. Results: When the tree canopy recovers, structure and composition of the vegetation also return to the long-since burned community; when tree canopy does not recover, composition of the post-ﬁre community varies compared to the long-since burned one. A higher proportion of obligate seeders in the pre- ﬁre community promotes quicker regeneration of the original community. The proportion of obligate seeders increased along the dryness gradient. Conclusions: Regeneration of plant communities after ﬁre depends on the vegetation type before the ﬁre. Regeneration increases when the dominant tree or shrub species persists after ﬁre and with a higher proportion of obligate seeders in the pre-ﬁre community. The proportion of obligate seeders varies along the dryness gradient, which suggests that vegetation in drier areas (when seeders are more abundant) recovers earlier than in moister areas.
Keywords: climatic gradient; community; nomenclature; obligate seeder; resilience; resprouter; Seeder

Soil seed bank and floristic diversity in a forest-grassland mosaic in southern Spain - Díaz-Villa, M. D.; MARAÑON, T.; Arroyo, J.; Garrido, B. (Journal of Vegetation Science, 2003)
Soil seed bank and floristic diversity were studied in a forest of Quercus suber, a forest of Quercus canariensis and a grassland, forming a vegetation mosaic in Los Alcornocales Natural Park, southern Spain. The soil seed bank was estimated by the germination technique. In each community patch, diversity, woody species cover and herbaceous species frequency was measured. Three biodiversity components – species richness, endemism and taxonomic singularity – were considered in the vegetation and the seed bank. Forest patches had a soil seed bank of ca. 11 200-14 100 seed.m–2 and their composition had low resemblance to (epigeal) vegetation. The grassland patch had a more dense seed bank (ca. 31 800 seed.m–2 ) and a higher index of similarity with vegetation, compared with the forests nearby. The complete forest diversity was 71-78 species on 0.1 ha, including 12-15 species found only in the seed bank; the grassland species richness was higher (113 species on 0.1 ha). We discuss the role of soil seed banks in the vegetation dynamics and in the complete plant biodiversity of the mosaic landscape studied.
Keywords: Biodiversity; forests conservation; mediterranean forest; nomenclature; Regeneration; Species richness

Soil seed bank and floristic diversity in a forest-grassland mosaic in southern Spain - Díaz-Villa, M D; MARAÑÓN, T; Arroyo, J; Garrido, B (Journal of Vegetation Science, 2003)
Soil seed bank and floristic diversity were studied in a forest of Quercus suber, a forest of Quercus canariensis and a grassland, forming a vegetation mosaic in Los Alcornocales Natural Park, southern Spain. The soil seed bank was estimated by the germination technique. In each community patch, diversity, woody species cover and herbaceous species frequency was measured. Three biodiversity components – species richness, endemism and taxonomic singularity – were considered in the vegetation and the seed bank. Forest patches had a soil seed bank of ca. 11 200-14 100 seed.m–2 and their composition had low resemblance to (epigeal) vegetation. The grassland patch had a more dense seed bank (ca. 31 800 seed.m–2 ) and a higher index of similarity with vegetation, compared with the forests nearby. The complete forest diversity was 71-78 species on 0.1 ha, including 12-15 species found only in the seed bank; the grassland species richness was higher (113 species on 0.1 ha). We discuss the role of soil seed banks in the vegetation dynamics and in the complete plant biodiversity of the mosaic landscape studied.
Keywords: Biodiversity; forests conservation; mediterranean forest; nomenclature; Regeneration; Species richness